Methane Flux Measurements, Happy Valley, AK, 1994 (Arctic Data Center, 2016)
This data set contains CH4 (methane) flux and related measurements taken at the Happy Valley Flux Study Site in northern Alaska during the summer of 1994. Sampling was conducted to test use of a laser sensor on a portable eddy correlation tower by assessing its practicality for sampling in remote flux studies. The flux-related variables measured were: wind direction and speed, friction velocity, air temperature, C02, H20, sensible and latent heat, and CO2 and CH4 flux. The Webb-Pearman-Leuning correction was applied to both the CO2 and CH4 fluxes.